Impact of COVID-19 on the Church of God in Nigeria - Falaye, T. A. (NIU Journal of Humanities; Vol 5 No 2 (2020): KIU Journal of Humanities, Vol. 5 No. 2, June 2020, 2020)
This paper explores the effects of Covid-19 in the Church with a bid to identifying the positives and negative influence on the Church, which is expected to be the community of faith. Covid-19 is a disease and death virus that has infected the world since early 2020. Governments around the world are finding it more difficult to deal with it, because it rising has different goals. However, the battle against this virus in Nigeria is becoming more daunting due to persistent difficulties such as pervasive socio-economic inequality, less importance of life being provided to those on the margins, and the government's apathic response. Otherwise, corona virus is both stubborn and untouchable. It's not afraid of strong regimes, riches of wealthy, advanced technology, war arsenals, nuclear weapons, strict rules, or violent police forces. So, who's going to win, the people or the virus? Ultimately, research can discover a cure, but in the meantime, the deadly virus is endangering democracies, undermining religion, economies, employment and businesses, destroying health, mental and social well-being, and killing thousands more on the planet due to fear or hunger, as well as to the dearth of medical facilities.